Peace in the Middle East : P2P and the Israeli-Palestinian conflict - Atieh, Adel (UNIDIR, 2005)
Examines the failure of the post-Oslo "people-to-people" (P2P) programmes organized by local NGOs with the aim of encouraging Israelis and Palestinians to a better understanding of one another and to begin a process of mutual reconciliation, and suggests ways the P2P programmes might be revised and renewed in the future